GPU Supported Simulation of Transition-Edge Sensor Arrays - Lorenz, Maximilian; Kirsch, Christian; Merino-Alonso, P. E.; Peille, P.; Dauser, Thomas; Cucchetti, E.; Smith, S. J.; Wilms, Jörn (Journal of Low Temperature Physics, 2020)
We present numerical simulations of full transition-edge sensor (TES) arrays utilizing graphical processing units (GPUs). With the support of GPUs, it is possible to perform simulations of large pixel arrays to assist detector development. Comparisons with TES small-signal and noise theory confirm the representativity of the simulated data. In order to demonstrate the capabilities of this approach, we present its implementation in xifusim, a simulator for the X-ray Integral Field Unit, a cryogenic X-ray spectrometer on board the future Athena X-ray observatory.
CRIS-Team WoS Importer:2020-04-24